Titanium dioxide immobilization in recycled aluminum net for degradation of textile dye by Heterogeneous Photocatalysis trough neural networks - Santana, Ingrid Larissa da Silva; Barbosa, Ada Azevedo; Silva, Marina Gomes; Aquino, Ramon Vinicius Santos de; Neves, Naiana Santos da Cruz Santana; Silva, Josivan Pedro da; Ferreira, Isis Henriqueta dos Reis; Rocha, Otidene Rossiter Sa da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
In this work, aluminum net crafted (recycled) were used as TiO2 support for the treatment of textile dye Remazol golden yellow (RGY 150). The immobilization of 200mg of TiO2 was accomplished after aluminum net calcination. The following experiments were carried out in a photocatalytic bench reactor: preliminary tests, a 23 factorial experimental design with best system and the degradation kinetic in systems with TiO2 supported on aluminum net.It was observed characteristic peaks of aluminum and TiO2 (anatase and rutile) by XRD and the catalyst film formation was verified by SEM. The system UV/H2O2/TiO2 performed higher efficiency, with 99% of dye degradation in 50 minutes, followed by the system UV/H2O2/TiO2sp with 93% of dye degradation. Whereas the supported catalyst presents execution advantages and high degradation rates, the factorial design was realized for this system, displaying best degradation (100% degradation in 35 minutes). It was obtained k = 0.114 min-1 and R² = 0.994 in a pseudo-first-order model adjustment system. The use of artificial neural network was proven to be efficient to predict the degradation of a textile dye, with an absolute error of 0.0181. After treatment, there was a decrease of dye toxicity.